OP74 Understanding the process of developing and implementing chronic disease policies in the caribbean region: a qualitative policy analysis. (2nd September 2017) - Guell, C; Murphy, MM; Samuels, TA; Bishop, L; Unwin, N
Abstract : Background: The Caribbean, like other middle income regions, experiences a significant burden of non-communicable diseases (NCDs), and responded in 2007 with a heads of government declaration committing to a range of policy measures. In 2015, this multi-method qualitative evaluation study investigated the progress made in seven Caribbean countries; this paper reports the findings of an analysis of the process that helped or hindered the development and implementation of policies. Methods: We conducted analysis of relevant policy documents, and 76 semi-structured interviews with 80 stakeholders from government (ministries of health, education); civil society (academia, agricultural, health and church organisations) and private businesses. Interviews were conducted by two regional teams. The initial pragmatic coding and categorisation of data with the software Dedoose was deductively framed by the WHO NDC Action Plan, and guided by a Multiple Streams policy approach and realist principles. This was complemented by further inductive thematic analysis and synthesis by the authors. Results: Two overarching themes emerged related to the process that guided the development, adaptation and implementation of regional policy goals into local settings.First, stakeholders reported a commonly shared recognition of the need for multi-sectoral partnerships but were frustrated by the difficulties of achieving this in practice. Country-specific NCD commissions served as case studies for both positive experiences of achieving 'whole of society' collaboration and difficulties in equitable representation and translation into government-led action. In settings with more effective multi-sectoral working it was possible to identify 'policy entrepreneurs' who had the profile and traction to promote cross sectoral action. Second, stakeholders highlighted the importance and opportunity provided by policy transfer . When comparing policy creation across small islands, most success has been made in areas such as tobacco control that could use an international framework and roadmap as a template. As policy efforts were most advanced in larger, more resource-rich countries, some stakeholders called for more synergetic working on policy solutions across countries. They felt that policy transfer could be improved in a region of relatively small countries but benefitting from a strong regional agenda, cooperation and professional exchange. Conclusion: Stakeholders' local and regional insight, expertise and experience helped to explain the processes that supported or hindered effective policy-making in different settings or different policy areas. Triangulating their reflections with a document review helped to corroborate and strengthen their assessment, provide contextual information to reports and also identified gaps in documentation and narratives.